The Impact of Burnout on Critical Care Nurses: Exploring Resiliency and Intervention Strategies - Hayat Ahmed Gamari Hakami , Salha Obayed Ali Albishi , Haitham Marzouq Alotaibi , Mona Saeed Alqahtani , Jaber Ali Hulal , Shamah Yahya Hassan Mangis , Fahad Muhammad Mansour Al-Dosari; Shuruq Maashi Alanazi , Raween Osama Balkhi , Zuhur Oudah Sanad Al-Yanbaawi; Haya Salem Mathker Alshahrani , Ebtsam Sultan Mohammed Alaklobi , Aisha Sultan Mohammed ALaklobi , Jawaher Mualaa Alkhaldi , Hamedh Ahmeed Hameed Alabsi (Journal of International Crisis and Risk Communication Research, 2024)
Burnout among critical care nurses is a growing concern with significant implications for both nurse well-being and patient safety. This scoping review investigates the causes, effects, and strategies related to burnout and resilience in critical care settings. It identifies key factors contributing to burnout, including high workloads, emotional exhaustion, moral distress, and organizational challenges such as staffing shortages. The review also highlights the role of resilience in managing burnout, with strategies like mindfulness, physical activity, and team-building exercises showing promise in improving nurse resilience. Organizational support, particularly in the form of appropriate staffing ratios and leadership fostering a supportive environment, is critical in preventing burnout. The findings underscore the need for both individual and organizational interventions to promote nurse well-being and enhance patient care in critical care environments. Future research should focus on preventive measures and evaluate the effectiveness of different resilience strategies.